Beyond crisis : achieving renewal in a turbulent world - Ringland, Gill.; Lustig, Patricia; Sparrow, Oliver (Chichester, West Sussex, UK ; Hoboken, NJ : John Wiley, 2010)
""If you want to know how countries, companies and individuals can master the winds and the waves that will dominate the next decade, this is the book for you.""--Rupert Pennant-Rea, former editor of the Economist, Deputy Governor of the Bank of England ""'If leading your organisation sometimes feels like changing the front wheel of a bicycle whilst toy are still pedalling it as fast as you can, this is a book you should read.""-Sir David Brown, former Chairman, Motorola UK ""Beyond Crisis is full of compelling reasons, clear advice and practical models to help
A short history of the crisis -- The new operating environment demographics -- What lies ahead? -- Organisational design -- The foxes and hedgehogs of renewal -- The importance of purpose -- Five qualities for renewal --The structure of renewal -- Managing renewal -- Values -- Insight -- Generating options -- Narrative -- Machinery -- Conclusion : a purposeful self-renewing organisation.
Includes bibliographical references.
Print version record.
John Wiley and Sons
Keywords: Financial crises -- United States; Finance -- Government policy -- United States; Bank failures -- United States; Intervention (Federal government) -- United States; Finances -- Politique gouvernementale; Banques -- Faillites; z; BUSINESS & ECONOMICS -- Corporate Governance; BUSINESS & ECONOMICS -- Leadership; BUSINESS & ECONOMICS -- Organizational Development; BUSINESS & ECONOMICS -- Workplace Culture; Bank failures; Finance -- Government policy; Financial crises; Intervention (Federal government); United States